Interpretive Paradigms in Accounting Research Methodology: A Philosophy of Science Approach – Gadamer's Hermeneutics - Yudi, Yudi (Green Publisher Indonesia, 2023)
This article discusses interpretive paradigms in accounting science research methodology. The methodology discussed refers to the philosophy of hermeneutics developed by Hans-Georg Gadamer, namely subjective hermeneutics. One of the developments in the philosophy of hermeneutics is adopted its application to the field of accounting through an intrerpretive paradigm. The discussion in this article is expected to enrich knowledge in the study of interpretation paradigms in the field of accounting with a hermeneutic approach.